A new dysferlin gene mutation in a Portuguese family with Miyoshi myopathy. Issue 7 (19th July 2021) - Ganchinho Lucas, Sandra; Vieira Santos, Inês; Pencas Alfaiate, Filipe Jorge; Lino, Ireneia
Abstract : Dysferlinopathies are autosomal recessive muscular dystrophies caused by mutations in the dysferlin gene (DYSF). A 33-year-old man was born to a non-consanguineous couple. At the age of 25 he stared to feel weakness of the distal lower limbs and also experienced episodes of rhabdomyolysis. Electromyography showed a myopathic pattern, and muscle biopsy revealed dystrophic changes with absence of dysferlin. Genetic analysis was positive for a mutation in the c3367_3368del DYSF gene (p.Lys1123GLUFS*2). After 8 years of disease evolution the symptomatology worsened. This is the first report of this mutation of the DYSF gene identified in a non-consanguineous Portuguese family, studied over 8 years. We believe the mutation is responsible for the Miyoshi myopathy. Disease progression cannot be predicted in either the patient or carrier family because there are no similar cases previously described in the literature.